Air-lake exchange of methane during the open water season in Syowa Oasis, East Antarctica - SASAKI, Masafumi; ENDOH, Noboru; IMURA, Satoshi; KUDOH, Sakae; YAMANOUCHI, Takashi; MORIMOTO, Shinji; HASHIDA, Gen (Journal of Geophysical Research, 2010)
Dissolved methane concentrations (DM) in 17 lakes were measured as a part of the operations of the 45th Japanese Antarctic Research Expedition in ice-free rocky areas along the eastern coast of Lutzow-Holm Bay (Syowa Oasis) in East Antarctica in the summer of 2003~2004. DM at the surfaces of 14 lakes ranged from the atmospheric equilibrium concentration (about 4 nmol L?1 for fresh water) to 385 nmol L?1. Relatively low DM of less than 50 nmol L?1 were observed at about 60% of the lakes. Many of the lakes (area fraction of 85%) were supersaturated and are thus sources of methane to the atmosphere. The exchange coefficient was calculated using wind speed data at Syowa Station. Area fraction frequency distributions with 4 surface DM ranges were applied to all lakes at Syowa Oasis (110 lakes: total lake area of 9 km2). Extrapolation to the whole Syowa Oasis gives an estimate of total emission of about 1 t-CH4 yr?1. This is the first estimation of methane flux from the surfaces of thawed lakes to the atmosphere in Antarctica. Since methane efflux of about 2 t-CH4 yr?1 from frozen bubbles in lake ice was estimated in our previous study, a total amount of 3 t-CH4 yr?1 would be released to the atmosphere from the lakes during the ice melting season (December ~ January) at Syowa Oasis. journal article